2019
DOI: 10.1029/2018ms001369
|View full text |Cite
|
Sign up to set email alerts
|

Global Mean Climate and Main Patterns of Variability in the CMCC‐CM2 Coupled Model

Abstract: Euro-Mediterranean Centre on Climate Change coupled climate model (CMCC-CM2) represents the new family of the global coupled climate models developed and used at CMCC. It is based on the atmospheric, land and sea ice components from the Community Earth System Model coupled with the global ocean model Nucleus for European Modeling of the Ocean. This study documents the model components, the coupling strategy, particularly for the oceanic, atmospheric, and sea ice components, and the overall model ability in rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 306 publications
(129 citation statements)
references
References 116 publications
2
115
0
Order By: Relevance
“…The mean net eastward transport of 155, 90 and 125 Sv, respectively, for LL, MM and MH models compares to the recent observational range of 173 ± 11 Sv (Donohue et al, 2016), with earlier estimates lacking a robust barotropic component (e.g. 137±8 Sv; Cunningham et al, 2003). Using the former measure, LL is closest to the observational range, while MM is only 40 % of it.…”
Section: Antarctic Circumpolar Currentsupporting
confidence: 62%
“…The mean net eastward transport of 155, 90 and 125 Sv, respectively, for LL, MM and MH models compares to the recent observational range of 173 ± 11 Sv (Donohue et al, 2016), with earlier estimates lacking a robust barotropic component (e.g. 137±8 Sv; Cunningham et al, 2003). Using the former measure, LL is closest to the observational range, while MM is only 40 % of it.…”
Section: Antarctic Circumpolar Currentsupporting
confidence: 62%
“…The fourth model is version 2 of the Euro-Mediterranean Centre on Climate Change Climate Model (CMCC-CM2; Cherchi et al 2018). It is composed of version 4 of the Community Atmosphere Model (CAM; Neale et al 2013), NEMO3.6 for the ocean, CICE4.0 for sea ice, and version 4.5 of the Community Land Model (CLM, Oleson et al 2013).…”
Section: Modelsmentioning
confidence: 99%
“…In order to demonstrate the role of TCs in drying the Maritime Continent, we also exploited GCM experiments. Although the CMCC-CM2 fully coupled model demonstrates a reasonable representation of the tropical mean climate and variability in both low (HR 110 km, CMIP5-like horizontal resolution) and high (28,16) [VHR 25 km, HighResMIP CMIP6like resolution (46,47)] resolution, the main difference between the two is the weakness of the lower-resolution model in representing the number and intensity of TCs (SI Appendix, Fig. S1).…”
Section: Tc-induced Drying Of the Maritime Continent: The Mechanismmentioning
confidence: 99%
“…We found that a net eastward water transport anomaly in the equatorial region of the west North Pacific (WNP), induced by TCs developing in the basin, may be responsible for a significant moisture flux divergence over the Maritime Continent, thus reducing the local precipitation during the onset of the dry season. We investigated this process using Japanese 55-y Reanalysis (JRA-55) (26) and conducted numerical experiments based on low-and highresolution versions of the Centro Euro-Mediterraneo per i Cambiamenti Climatici Climate Model 2 (CMCC-CM2) General Circulation Model (GCM) (16,27,28). Our findings suggest that forecasting TC activity in the WNP might also help in predicting the onset of the dry season over the Maritime Continent.…”
mentioning
confidence: 99%